Fellatio by fruit bats prolongs copulation time. - Min Tan (Public Library of Science (PLoS), 2009)
Oral sex is widely used in human foreplay, but rarely documented in other animals. Fellatio has been recorded in bonobos Pan paniscus, but even then functions largely as play behaviour among juvenile males. The short-nosed fruit bat Cynopterus sphinx exhibits resource defence polygyny and one sexually active male often roosts with groups of females in tents made from leaves. Female bats often lick their mate's penis during dorsoventral copulation. The female lowers her head to lick the shaft or the base of the male's penis but does not lick the glans penis which has already penetrated the vagina. Males never withdrew their penis when it was licked by the mating partner. A positive relationship exists between the length of time that the female licked the male's penis during copulation and the duration of copulation. Furthermore, mating pairs spent significantly more time in copulation if the female licked her mate's penis than if fellatio was absent. Males also show postcopulatory genital grooming after intromission. At present, we do not know why genital licking occurs, and we present four non-mutually exclusive hypotheses that may explain the function of fellatio in C. sphinx.